2016
DOI: 10.1002/adsc.201500957
|View full text |Cite
|
Sign up to set email alerts
|

Titania‐Supported Gold Nanoparticles Catalyze the Selective Oxidation of Amines into Nitroso Compounds in the Presence of Hydrogen Peroxide

Abstract: Dedicatedi nm emory of Prof.Y iannis Elemes,r emembering the stimulating scientific discussionsa nd friendship.Supporting information for this article is availableonthe WWW under http://dx.doi.org/10.1002/adsc.201500957.Abstract: In this article,t he catalytic activity of titania-supported gold nanoparticles (Au/TiO 2 )w as studied for the selective oxidation of aminesi nto nitroso compounds using hydrogen peroxide (H 2 O 2 ). Gold nanoparticles deposited on DegussaP 25 polymorphso ft itania (TiO 2 )h ave been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 104 publications
0
17
0
Order By: Relevance
“…As ac ontinuation of our interest in the heterogeneous catalyzed reductivet ransformations by supported gold ands ilver nanoparticles, [33] we introduce hereinfor the first time-A g/HMS-NaBH 4 as an efficient and highly active catalytic systemf or the selective 1,2-reduction of azines to the corresponding benzyl hydrazones,u nder mild conditions.R ecently,s ilver nanoparticles supported on aluminawere reported for the hydrogenation of imines to the corresponding amines,a lthough high temperature and pressure were required( Scheme 1). [34] In the combination of catalytic and synthetic points of view,t he presents elective heterogeneous reductionp rovidesa na lternative route towards the synthesiso fb enzylh ydrazones which offers advantages such as selectivity,recyclability,c leanc hemical synthesis, high isolated yields,u se of more stablep recursors avoiding harsh conditions and acidic additives.The catalytic results are interpreted on the basis of ak inetic analysis,a sw ell as on the product characterization by LC-MS andN MR spectroscopy.…”
Section: Introductionmentioning
confidence: 86%
“…As ac ontinuation of our interest in the heterogeneous catalyzed reductivet ransformations by supported gold ands ilver nanoparticles, [33] we introduce hereinfor the first time-A g/HMS-NaBH 4 as an efficient and highly active catalytic systemf or the selective 1,2-reduction of azines to the corresponding benzyl hydrazones,u nder mild conditions.R ecently,s ilver nanoparticles supported on aluminawere reported for the hydrogenation of imines to the corresponding amines,a lthough high temperature and pressure were required( Scheme 1). [34] In the combination of catalytic and synthetic points of view,t he presents elective heterogeneous reductionp rovidesa na lternative route towards the synthesiso fb enzylh ydrazones which offers advantages such as selectivity,recyclability,c leanc hemical synthesis, high isolated yields,u se of more stablep recursors avoiding harsh conditions and acidic additives.The catalytic results are interpreted on the basis of ak inetic analysis,a sw ell as on the product characterization by LC-MS andN MR spectroscopy.…”
Section: Introductionmentioning
confidence: 86%
“…It seems reasonable to assume that the same is true for the reaction we are considering. The transition state for formation of cation radical of type 1 is better stabilized by an electron‐donating group R bonded to the nitrogen atom . Taking this into account, the fact that the yield of glyphosate increases with increasing the + I effect of substituent R in the starting compound (Table , entries 1–4) can be considered as evidence for the proposed mechanism involving the formation of cation radical 1 in the rate‐determining step of the reaction.…”
Section: Resultsmentioning
confidence: 94%
“…In particular, they have been successfully applied for the oxidative transformations of amines utilizing O 2 as oxidant with the formation of various types of products, including oxidative N ‐formylation and synthesis of azo‐compounds, oxidation of the secondary amines to imines, aromatic and aliphatic tertiary amines to N ‐oxides and cyclic tertiary amines to lactams . Following this, Fountoulaki et al reported the gold‐catalyzed selective oxidation of primary amines with H 2 O 2 in MeOH to nitroso compounds. These findings clearly showed that gold is a catalyst allowing the selective oxidative conversion of one N ‐containing functional group into another.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in this topic can be quantitatively illustrated by the exponential growth in the number of relevant publications (Figure ). Nowadays, “yellow metal” is used as a catalyst for various reactions, such as oxidation of alcohols and aldehydes, selective hydrogenations, cyclization reactions, carbon‐nitrogen bond formation, and so on ,. In contrast to other metals, one of the most attractive features of Au NPs is the high selectivity during these processes, which allows fine discrimination with geometrical positions and chemical groups, helping to achieve high yields of the desired products.…”
Section: Introductionmentioning
confidence: 99%